Pertanian sebagai basis budaya bangsa Indonesia (Pemahaman pertanian kepada murid sebagai aspek fundamental keterampilan kewarganegaraan) - fandy adpen lazzavietamsi (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
Through agriculture, the independence of the Indonesian nation can be achieved, of course it must be supported by the use of agricultural technology and the use of agricultural products by all elements of society. Agriculture is very fundamental for the Indonesian people, and must be cultivated for the next generation of the nation. The civilizing effort is through civic education which has three development domains, namely civic knowledge, civic skills, and civic character. Among the three domains, citizenship skills are the right means for agricultural civilisation. Agriculture as a fundamental basis of citizenship skills is the ability of every young generation of the Indonesian nation to identify and describe, explain and analyze, evaluate, determine and maintain attitudes or opinions regarding public issues in a holistic manner that is useful not only for the survival of Indonesian people but also for the sake of survival. ecology in Indonesia. The strategy of agricultural culture as a cultural basis for citizenship skills must be implemented through various levels and educational pathways by utilizing the concept of green education.